PERAN RTH DALAM MITIGASI EMISI GRK : STUDI KASUS PT INKA PABRIK BANYUWANGI - Afif Pratama Tris Ardiansyah; Muhammad Abdus Salam Jawwad (CV SWA Anugerah, 2025)
One of the main obstacles to climate change mitigation is the increasing greenhouse gas (GHG) emissions from industrial activities. The purpose of this study was to determine the total greenhouse gas emissions produced by the PT INKA Factory in Banyuwangi and to examine how well the factory's Green Open Space (GOS) absorbs carbon dioxide (CO₂). The calculation of GHG emissions uses the IPCC Tier 1 guidelines with default emission factors, while the type of vegetation and land cover area are used to assess the potential of GOS to absorb carbon. The results of the study show that the company's operational activities produce annual GHG emissions of 846,566 tons of CO₂-eq, with the largest portion of emissions coming from electricity consumption. Meanwhile, the existing RTH can absorb 2.981,53 tons of CO₂. Along with the development of the company's operations, the RTH development plan is projected to increase the carbon absorption capacity to 4.319,88 tons of CO₂ per year, so that it is expected to be able to offset the potential for increased emissions in the future.